Ultra-high strength circular short CFST columns: Axisymmetric analysis, behaviour and design. (15th January 2019) - Patel, V.I.; Hassanein, M.F.; Thai, Huu-Tai; Al Abadi, H.; Elchalakani, M.; Bai, Y.
Highlights: Axisymmetric model for circular CFST short columns with UHSC is developed. UHSC in CFST columns reduces the section area by 50% when compare with NSC. Steel contribution ratio above 0.3 is needed to ensure ductility of UHSC. Australian and European codes safely predict strength of CFST column with UHSC. Abstract: A nonlinear axisymmetric simulation of axially loaded ultra-high strength circular short Concrete-Filled Steel Tubular (CFST) columns is reported in this paper. An efficient material law of Ultra-High Strength Concrete (UHSC) is employed in this axisymmetric simulation to consider the confining effects which increase the ultimate strain, stress and axial ductility. The peak loads and load-strain responses of short CFST columns predicted by the axisymmetric model are verified with the independent test data and those predicted by the three-dimensional (3D) model. The structural characteristics of circular short CFST columns having different material and geometric parameters are subsequently examined by the axisymmetric analysis. The numerical results indicate that the column size can approximately be reduced by 50% when UHSC is used in the composite construction instead of Normal Strength Concrete (NSC). Comparisons of the current test data are made with the current structural codes including AS/NZS 5100.6, Eurocode 4, AISC and GB 50936. The comparisons demonstrate that the Australian/New Zealand and European design codes provide consistent predictions for the ultimate axial strengths of ultra-high strength circular short CFST columns. On the other hand, the North American design code is conservative, whereas the Chinese code is unconservative.